2012
DOI: 10.1017/s0950268812002105
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and molecular detection of Mycobacterium bovis in cattle with inconclusive results to intradermal tuberculin tests

Abstract: A dairy herd (77 cows) from Rio de Janeiro, Brazil, with a history of tuberculosis infection was tested by a comparative cervical test (CCT). Seventeen cows were reactive and seven were inconclusive (swelling ≥ 2.0 mm and ≤ 3.9 mm, respectively). All of these 24 cows were slaughtered and necropsied ; samples from lungs and lymph nodes were collected for multiplex polymerase chain reaction (PCR) and culturing. Infection was confirmed in 23/24 (95.8%) of the slaughtered animals (five by culturing, four by PCR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…Similar findings were reported in Brazil when six out of seven inconclusive cases by the skin test, were positive by PCR and culture (Zarden et al, 2013). Medeiros et al (2010) reported that anergic animals may be harbouring TB, yet were not reactive to the skin test; while delayed hypersensitivity may take 3 to 6 weeks, following infection (OIE, 2009).These are probable reasons for obtaining inconclusive results in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were reported in Brazil when six out of seven inconclusive cases by the skin test, were positive by PCR and culture (Zarden et al, 2013). Medeiros et al (2010) reported that anergic animals may be harbouring TB, yet were not reactive to the skin test; while delayed hypersensitivity may take 3 to 6 weeks, following infection (OIE, 2009).These are probable reasons for obtaining inconclusive results in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Fráguas et al (2008) indicated that, from a total of 97 bovine animals reactive to the intradermal test, only 11.34% (11/97) were confirmed as M. bovis in bacterial cultures and postulated that this low bacterial recovery rate may be related to the difficulty of carrying out M. bovis cultures, which requires a minimum amount of viable bacilli, in addition to a decontamination technique applied during the process that can render this microorganism unfeasible. Zarden et al (2013) followed the slaughter of 24 cattle reactive to the tuberculin skin test, with 29.16% (n = 7) presenting suspicious lesions for bTB. When submitting samples without lesions for laboratory analysis, it was found that 73.16% (n = 19) of the animals tested positive when using bacterial culture, while 75.16% (n = 18) tested positive by the molecular method.…”
Section: Bivariate Analysismentioning
confidence: 99%
“…Humans acquire the infection through contact with aerosols expelled by infected animals or mainly, through the consumption of milk and dairy products not pasteurized or not heat treated from contaminated animals. It is, therefore, a serious public health problem, considered a cosmopolitan and re-emerging zoonosis (Medeiros, Marassi, Figueiredo, & Lilenbaum, 2010;Zarden, Marassi, Carvalho, Figueiredo, & Lilenbaum, 2013;Carvalho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Humans acquire the infection through contact with aerosols expelled by infected animals or mainly, through the consumption of milk and other foods from contaminated animals. It is, therefore, a serious public health problem, as it is a zoonosis (Medeiros et al 2010; Zarden et al 2013;Carvalho et al 2016).…”
Section: Introductionmentioning
confidence: 99%